Identification of RRII 400 series clones of Hevea brasiliensis in the early growth phase - Thomas V; Gireesh T; Meenakumari T; Varghese Y A (Placrosym XVII, 2006, Kochi, India. Journal of Plantation Crops, 34 (3). Indian Cardamom Research Institute (Spices Board), Idukki, India, pp.198-204.)
The recently evolved hybrid clones of RRII 400 series viz., RRII 414, RRII 422, RRII 429 and RRII 430 of parents RRII 105 and RRII 100 have shown an average yield improvement of more than 20 percent over RRII 105. Among these, RRII 414 and RRII 430 were released for cultivation in 2005 and the others are in the pipeline. The present study was undertaken using one year old field plants with the objective of facilitating the identification of these clones recommended for commercial cultivation. Qualitative morphological traits viz., leaf characters including leaf storey, leaf scar, shape of the leaves and pattern of venation were recorded. Results indicate marked distinction between the clones with respect to morphological traits. A combination of specific traits could be used for identification of each clone. Leaf characteristics of RRII 414 shows a close affinity to the female parent RRII 105 while RRII 429 and RRII 430 shows more resemblance to the male parent RRIC 100. The remaining two clones viz, RRII 417 and RRII 422 were intermediate for these characters.
Keywords: Clone identification; Qualitative morphological traits; RRII 400 series clones